(Pengaruh Model Game Based Learning (GBL) Berbantuan Baamboozle Terhadap Student Engagement dan Hasil Belajar Siswa Mapel Pendidikan Pancasila Kelas II SD Negeri Pulo 01 Lumajang) - Dian Indah Safitri (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This research aims to test the effect of the model Game Based Learning (GBL) assisted by Baamboozle against student engagement and student learning outcomes in learning Pancasila Education. The research design uses quasi experimental with models Pretest and Posttest Nonequivalent Control Group Design. Sampling was taken using a census/sampling technique totaling 25 students in class II of SD Negeri Pulo 01 Lumajang. Data collection uses questionnaires and tests. The data analysis technique uses the t-test or independent sample t-test with software SPSS version 26. The results of this research show that 1) Student engagement in the experimental class using the model Game Based Learning (GBL) assisted by Baamboozle with an average score of 87.48, while the control class used the learning model cooperative learning type with an average value of 79.24; 2) Learning outcomes of experimental class students who use the model Game Based Learning (GBL) assisted by Baamboozle with an average score of 80.80, while the control class used a learning model cooperative learning type with an average score of 69.80. On test-t shows that the probability value (sig.) in the experimental group is (0.006 < 0.05) at posttest student engagement and equal to (0.001 < 0.05) on the posttest of student learning outcomes. Therefore, it is concluded that there is a significant influence on student engagement and student learning outcomes taught using the model Game Based Learning (GBL) Assisted by Baamboozle. This research recommends that the model Game Based Learning (GBL) With the help of Baamboozle, it can be a reference for increasing student engagement, active learning, and student-centered learning so that the learning process becomes interactive, fun, and able to maximize the role of technology in education.
Reaploud Repository February 2026_Hasyim
Keywords: Game Based Learning (GBL); Baamboozle; Student Engagement; Learning outcomes